Identification of Key Biomarkers and Pathways for Maintaining Cognitively Normal Brain Aging Based on Integrated Bioinformatics Analysis - Xu, Jinling; Zhou, Hui; Xiang, Guangda (Frontiers in Aging Neuroscience, 2022)
Background: Given the arrival of aging population has caused a series of social and economical problems, we aimed to explore the key genes underlying cognitively normal brain aging and its potential molecular mechanisms. Methods: GSE11882 was downloaded from GEO. The data from different brain regions was divided into aged and young groups for analysis. Co-expressed differentially expressed genes (DEGs) were screened. Functional analysis, PPI network, miRNA-gene and TF-gene networks were performed to identify hub genes and related molecular mechanisms. AlzData database was used to elucidate the expression of DEGs and hub genes in aging brain. Animal studies were conducted to validate the hub genes. Results: Co-expressed DEGs contained 7 upregulated and 87 downregulated genes. The enrichment analysis indicated DEGs were mainly involved in biological processes and pathways related to immune inflammatory responses. From PPI network, 10 hub genes were identified: C1QC, C1QA, C1QB, CD163, FCER1G, VSIG4, CD93, CD14, VWF and CD44. CD44 and CD93 were the most targeted DEGs in miRNA-gene network, and TIMP1, HLA-DRA, VWF, and FGF2 were the top four targeted DEGs in TF-gene network. In AlzData database, the levels of CD44, CD93 and CD163 in AD patients were significantly increased than those in normal controls. Meanwhile, in the brain tissues of cognitively normal mice, the expression of CD44, CD93 and CD 163 in aged group were significantly lower than those in young group. Conclusion: The underlying molecular mechanisms for maintaining healthy brain aging are related to the decline of immune inflammatory responses. CD44, CD93 and CD 163 are considered as the potential biomarkers. Our study provides more molecular evidence for maintaining cognitively normal brain aging.